Clinical performance of the BioFire Blood Culture Identification 2 panel for microorganism species identification and resistance gene detection in blood culture-positive specimens - Haruki Naruse; Noriyuki Watanabe; Sachie Koyama; Sachi Tanaka; Yoshitada Taji; Yasuhiro Ebihara (PLoS ONE, 2026)
Introduction Bloodstream infections are life-threatening, and the rapid identification of pathogens and resistance genes is essential for the administration of appropriate antimicrobial agents. The BioFire Blood Culture Identification 2 (BCID2) panel on the FilmArray multi-parameter genetic analyzer is a fully automated PCR test that rapidly identifies species and resistance genes. Here, we compared the performance of the Filmarray BCID2 panel (BCID2 method) with the conventional method. Methods Among the blood culture-positive specimens submitted between January 2023 and November 2024, this study analyzed 201 specimens that contained the target microorganisms of the BCID2 panel. In our laboratory, after subculturing the culture medium obtained from a positive blood-culture bottle, we perform species identification using mass spectrometry and drug susceptibility testing (the conventional method). We compared the results of the BCID2 method with those of the conventional method. Results Concordance between the BCID2 and conventional methods was found in 152 of the 161 monomicrobial specimens (94.4%) and in 31 of the 40 polymicrobial specimens (77.5%). The 18 specimens that were discordant were mostly matched at the genus level, but the BCID2 method also detected other microorganisms that were not identified by the conventional method. Resistance genes were identified in 57 of the 61 matched specimens (93.4%). Conclusion The BCID2 method exhibits excellent identification results and resistance gene detection rates, suggesting that it is a reliable and rapid diagnostic test system for bloodstream infections.